ENHANCING INTERPERSONAL RELATIONSHIPS - Dilfuza Madgafurova (Galaxy International Interdisciplinary Research Journal, 2023)
Interpersonal relationships represent a fundamental aspect of human existence, significantly influencing our overall well-being and life satisfaction. This scientific article aims to explore the latest research and provide evidence-based strategies for improving interpersonal relationships. Drawing upon neuroscientific findings, we discuss the key factors that contribute to successful relationships and propose practical interventions that can enhance communication, empathy, trust, and conflict resolution skills. Overall, this scientific article explores the importance of interpersonal relationships and provides practical strategies for enhancing them based on neuroscientific research. The article covers various topics, including the neural substrates of social bonds, the role of empathy and perspective-taking, effective communication and active listening, building and maintaining trust, and conflict resolution and emotional regulation. By implementing evidence-based interventions in these areas, individuals can improve their relationship dynamics and overall well-being. The article concludes by highlighting the need for continued research in this field to further refine our understanding and provide novel insights into nurturing and improving interpersonal relationships.